2018
DOI: 10.1155/2018/3671892
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Intake Ameliorates Hyperglycemia and Insulin Resistance in WBN/Kob-Leprfa/fa Rats: A New Model of Type 2 Diabetes Mellitus

Abstract: High-salt intake is a major risk factor for developing hypertension in type 2 diabetes mellitus, but its effects on glucose homeostasis are controversial. We previously found that high-salt intake induces severe hypertension in WBN/Kob diabetic fatty (WBKDF) rats. In the present study, we examined the effects of a high-salt intake on glucose homeostasis in WBKDF rats. Male WBKDF rats and age-matched Wistar rats at 6 weeks of age were each divided into two groups and fed either a normal-sodium (NS, 0.26%) diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…Sodium pentobarbital is the most common anesthetic agent used before rodent's euthanasia by exsanguination 15 . As reported in several current literatures, sodium pentobarbital is used with different dosages which may impact the study parameters 16,17 . Thereby, the present study aimed to specify the optimum dosage of sodium pentobarbital that can be used while performing exsanguination with the least adverse effects on biochemical, molecular and histological measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium pentobarbital is the most common anesthetic agent used before rodent's euthanasia by exsanguination 15 . As reported in several current literatures, sodium pentobarbital is used with different dosages which may impact the study parameters 16,17 . Thereby, the present study aimed to specify the optimum dosage of sodium pentobarbital that can be used while performing exsanguination with the least adverse effects on biochemical, molecular and histological measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It is the major cause of high blood pressure, leading to cardiovascular diseases [7] and is related to an increased risk of obesity [8]. However, several recent lines of evidence have shown beneficial effects of a high-salt diet, such as reducing hyperglycemia, insulin resistance, and fat deposition [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have found an inverse association between dietary sodium intake and insulin resistance. In a recent 7-week experimental study, Yoshiichi et al demonstrated that high salt intake improved insulin sensitivity, and attributed this improvement to increased plasma levels of adiponectin [47]. Other previous studies, also conducted during short period, have come to a similar conclusion, demonstrating significant association of low-salt diet with higher homeostasis model assessment index [49].…”
Section: Discussionmentioning
confidence: 80%
“…The following pathophysiological mechanisms could explain this correlation: low sodium consumption lowers blood leptin levels, which leads to a reduction in the size of abdominal fat cells, leading to a decrease in obesity and insulin resistance [46]. Conversely, a high sodium intake would lead to an increase in the blood level of leptin [47] and therefore an increase in insulin resistance. In addition, a low sodium diet regulates the expression of the type 4 glucose transporter (GLUT4), the insulin receptors in fat cells, resulting in a decrease in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%